2020
DOI: 10.1038/s41467-020-19279-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal DNMT3A-dependent de novo methylation of the paternal genome inhibits gene expression in the early embryo

Abstract: De novo DNA methylation (DNAme) during mammalian spermatogenesis yields a densely methylated genome, with the exception of CpG islands (CGIs), which are hypomethylated in sperm. While the paternal genome undergoes widespread DNAme loss before the first S-phase following fertilization, recent mass spectrometry analysis revealed that the zygotic paternal genome is paradoxically also subject to a low level of de novo DNAme. However, the loci involved, and impact on transcription were not addressed. Here, we emplo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 87 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…Here we showed that the post-fertilization imprinted methylation we previously reported in mouse and human H19 ICRs also occurred in the mouse IG-DMR. Recently, whole-genome bisulfite sequencing analysis of a mouse pre-implantation embryo revealed that a number of genomic regions were de novo methylated on the paternal allele after fertilization [39]. Thus, post-fertilization DNA methylation that occurs against genome-wide reprogramming activity, may be an essential mechanism ensuring accurate gene expression in the early embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that the post-fertilization imprinted methylation we previously reported in mouse and human H19 ICRs also occurred in the mouse IG-DMR. Recently, whole-genome bisulfite sequencing analysis of a mouse pre-implantation embryo revealed that a number of genomic regions were de novo methylated on the paternal allele after fertilization [39]. Thus, post-fertilization DNA methylation that occurs against genome-wide reprogramming activity, may be an essential mechanism ensuring accurate gene expression in the early embryos.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the maternal genome in the control zygotes exhibited a slight methylation increase during the transition from oocyte to zygote. Despite the global loss of methylation in the zygotic pronuclei, de novo methylation has been observed in a subset of regions in the paternal genome, and it is believed that DNMT3A and DNMT1 are required for such de novo methylation [ 43 , 44 ]. DNMT3A was located in both parental pronuclei [ 44 ], implying that de novo methylation might also occur in the maternal genome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the global loss of methylation in the zygotic pronuclei, de novo methylation has been observed in a subset of regions in the paternal genome, and it is believed that DNMT3A and DNMT1 are required for such de novo methylation [ 43 , 44 ]. DNMT3A was located in both parental pronuclei [ 44 ], implying that de novo methylation might also occur in the maternal genome. In this study, we found new methylated sites arising in the maternal genome after fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several dozen CpG-rich promoters are de novo methylated by maternal DNMT3A on the paternal allele of the 2-cell embryo. Loss of maternal DNMT3A leads to a premature transcription of these paternally-expressed genes at the 4-cell stage 166 . In another study, the oocytes of hyperglycemic mice or from humans with diabetes, showed reduced expression of T et3 deoxygenase.…”
Section: Influence Of Sperm-inherited Epigenetic Factors On Embryonic...mentioning
confidence: 99%